A parentalidade paterna na separação conjugal quando os filhos coabitam com o genitor - Vilaça, Carolina Corrêa (2018)
Everyday more and more fathers express their desire to continue living and getting involved in their children's lives, even though facing a marital breakdown. We can also verify an increase in the number of fathers who have shown a wish in taking care of their children after separation because they feel as much capable as the mothers. However, it is known that, despite the mandatory shared custody in Brazil, the reference residence still continues, in the most of cases, being in the maternal one. Perhaps because of this fact there is still little information about paternal parenting, in the context of marital separation, when the children live with the father. The present study aimed to describe how paternal parenting is experienced in the context of conjugal separation when the children live with the father from the perspective both of the father and the children. Six families participated of the study. The father and one of his children between the ages of 9 and 12 were interviewed. It was established as an inclusion criterion that at least one of the children in this age group was in fact under the custody of the father. The fathers were aged between 31 and 35 years old and answered to a semi-structured interview script, composed by themes related to the sociodemographic characterization, characteristics of the exercise of parenthood before and after separation, routine and parent / child relationship, relationship parenting, participation of other family members in caring of the children and other contexts. It was also applied, in all of the participants, an interview to survey the ecological contexts and their interrelationships, which were adapted for the purpose of this research, aiming to evaluate which contexts of coexistence were significant for fathers and children and how they contributed to the exercise of parenting. All the participants accepted to enroll voluntarily of the research and signed the Term of Free and Informed Consent and the Term of Free and Clarified Assent. The analysis of parents' and children's interviews was done based on the Content Analysis. After reading and analyzing the material, the reports were organized into categories for the two groups of participants, considering the most important themes for the research objectives: being a father, post-separation parenting and routine impacts, such as how did the children start living with the father, and what changed in the relationship, childcare, limits and control, activities that they carry out together, fathers and children relationship, main challenges, role of the biological mother in the life of the children, evaluation that biological mothers do on parental care. As main results it was found that the fathers who took the children after the separation felt a greater responsibility and reorganized their life in order to attend the children's needs. For those they had the help and support of third parties, especially of stepmothers, grandmothers and caregivers. In addition, these parents were committed not only to the role of providing and disciplining, but also to the affective aspect of the relationship. They have faced the challenges of taking parental care after separation and reconciling work and time available to their children. It was found that both fathers and children understood the relationship to be close and positive. Considering the bioecological theory of development, the father's house, comprehended as a microsystem, encouraged and provided meaningful interactions, enabling the proximal processes to promote the development of children and fathers. It was concluded that the research made possible the expansion of information regarding paternal parenting in the context of separation when children live with the father, contributing to the knowledge about the subject. It was also pointed out that consideration from the point of view of fathers and children provided a broader understanding of the context, since the relationships are two-way, having influence in both directions.